The atherogenic role of immune cells in familial hypercholesterolemia. Issue 4 (21st October 2019) - Taghizadeh, Eskandar; Taheri, Forough; Gheibi Hayat, Seyed Mohammad; Montecucco, Fabrizio; Carbone, Federico; Rostami, Daryoush; Montazeri, Ardalan; Sahebkar, Amirhossein
Abstract: Familial hypercholesterolemia (FH) is an autosomal dominant disorder of lipoprotein metabolism that mainly occurs due to mutations in the low‐density lipoprotein receptor gene and is characterized by increased levels of low‐density lipoprotein cholesterol, leading to accelerated atherogenesis and premature coronary heart disease. Both innate and adaptive immune responses, which mainly include monocytes, macrophages, neutrophils, T lymphocytes, and B lymphocytes, have been shown to play a key role for the initiation and progression of atherogenesis in the general population. In FH patients, these immune cells have been suggested to play specific pro‐atherosclerotic activities, from the initial leukocyte recruitment to plaque rupture. In fact, the accumulation of cholesterol crystals and oxLDL in the vessels in FH patients is particularly high, with consequent abnormal mobilization of immune cells and secretion of various pro‐inflammatory and chemokines. In addition, cholesterol accumulation in immune cells is exaggerated with chronic exposure to relevant pro‐atherosclerotic triggers. The topics considered in this review may provide a more specific focus on the immune system alterations in FH and open new insights toward immune cells as potential therapeutic targets in FH.